2009
DOI: 10.1021/ac901909j
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Transfer Voltammetric Behavior of Protein Digests at Liquid|Liquid Interfaces

Abstract: The development of new methods for the detection of proteins and peptides is of widespread importance. In this work, the electrochemical behavior of peptide mixtures resulting from proteolytic digestion of proteins was investigated at the polarized liquid|liquid interface (or the interface between two immiscible electrolyte solutions, ITIES). The influence of pepsin digestion on three proteins (hemoglobin, lysozyme, and cytochrome c) was studied, and it was revealed that resulting cyclic voltammograms of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…60 Hartvig et al 52 employed an online mass spectrometry method to detect protein-anion Herzog et al investigated this scenario, by denaturing proteins with urea 61 and by enzymatic digestion. 62 Indeed, it was found that the signals for these denatured or digested proteins were different from those of the native proteins. However, it must be borne in mind that when examining the electrochemistry of a protein in an acidic aqueous phase in contact with an organic phase, there is considerable scope for at least partial denaturation in the acidic phase and in contact with the interface, irrespective of any intentional denaturation using regular denaturants such as urea.…”
Section: Mechanism Of Protein Electrochemistry At the Itiesmentioning
confidence: 99%
“…60 Hartvig et al 52 employed an online mass spectrometry method to detect protein-anion Herzog et al investigated this scenario, by denaturing proteins with urea 61 and by enzymatic digestion. 62 Indeed, it was found that the signals for these denatured or digested proteins were different from those of the native proteins. However, it must be borne in mind that when examining the electrochemistry of a protein in an acidic aqueous phase in contact with an organic phase, there is considerable scope for at least partial denaturation in the acidic phase and in contact with the interface, irrespective of any intentional denaturation using regular denaturants such as urea.…”
Section: Mechanism Of Protein Electrochemistry At the Itiesmentioning
confidence: 99%
“…Electrochemistry at ITIES has also been used to investigate chemical denaturation, (149) enzymatic proteolysis of proteins, (150) and protein unfolding. (151) Complexation of DNA with acridine-functionalized calixarene has also been investigated at ITIES.…”
Section: Macromolecule Sensingmentioning
confidence: 99%
“…These interactions between lipophilic anions and proteins adsorbed at the interface were confirmed by biphasic electrospray ionization mass spectrometry [17], where adsorbed lysozyme molecules form complexes with tetrakis(4-chlorophenyl)borate (TPBCl -) of stoichiometry 1:1, 1:2 and 1:3 (lysozyme:TPBCl -). Recent studies have demonstrated that the electrochemical response of proteins at the ITIES is greatly influenced by disruptions of their structure, whether achieved by the presence of a chemical denaturant [18] or by proteolysis [19]. In the presence of urea, the electrochemical behaviour of Hb was greatly altered leading to a lower peak current and charge [18].…”
Section: Introductionmentioning
confidence: 99%